Phytate degradation, myo-inositol release, and utilization of phosphorus and calcium by two strains of laying hens in five production periods - Vera Sommerfeld (Poultry Science, 2020)
The objective of this study was to compare 2 laying hen strains in 5 production periods regarding phytase activity, phytate (InsP6) degradation, and myo-inositol (MI) release in the digestive tract and phosphorus (P) and calcium (Ca) utilization. One offspring of 10 nonrelated roosters per strain (Lohmann Brown-classic (LB) or Lohmann LSL-classic (LSL)) was placed in one of 20 metabolic units in a completely randomized block design in week 8, 14, 22, 28, and 58 of life. All hens were fed the same corn and soybean meal–based diet at one time, but the diet composition was adjusted to the requirements in the respective period. For 4 consecutive days, excreta were collected quantitatively at 24-hour intervals. In week 10, 16, 24, 30, and 60, the blood plasma, digesta of crop, gizzard, jejunum, ileum, and ceca, and mucosa of the jejunum was collected. The concentration of inorganic P in the blood plasma was higher in LB than in LSL hens (P = 0.026). Plasma Ca concentrations increased with each period (P < 0.001) in both strains. In jejunum digesta, the MI concentration did not differ between strains, but InsP6 concentration was higher in LB than in LSL hens (P = 0.002) and the highest in week 30 and 60. Total phosphatase and phytase activities were higher in LB than in LSL hens (P ≤ 0.009). Period effects were also significant for these enzymes. Concentrations of some constituents of the cecal content were different between the strains. The MI concentration in the egg albumen and yolk was higher in LB than in LSL hens. Differences in InsP6- and MI-related metabolism of the 2 hen strains existed. These differences were partly dependent of the period. Especially, week 24 was a period of remarkable change of metabolism. Great differences also existed among individuals, making it worth to have a closer look at the metabolism of individuals in addition to evaluating treatment means. Further studies on metabolic, genetic, and microbiome level may help explain these differences.